Flexibility focused stretching games for beginner rhythmic gymnasts - Sharifullina, S. R.; Zhestkova, Yu. K.; Razzhivin, O. A.; Chernyshova, S. Sh. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to improve the methodology of flexibility development at the initial stage of training of junior rhythmic gymnasts aged 5-6 years through the application of the stretching game elements. Methods and structure of the study. The study was carried out at the premises of the municipal budgetary institution "Sports School No. 1" of the Elabuga municipal district of the Republic of Tatarstan. Sampled for the study were the 5-6 year-old girls engaged in rhythmic gymnastics. The Experimental and Control Groups were made, homogeneous in terms of physical development indices, 15 subjects each. Physical exercises to determine the level of development of flexibility were selected as tests.